The role of polymer nanocomposites in sustainable wax deposition control in crude oil systems - systematic review - Abubakar Aji; Mysara Eissa Mohyaldinn; Hisham Ben Mahmud (AIMS Environmental Science)
The extraction and utilization of crude oil are fundamental to global energy production, driving economies and fueling countless industries. However, wax deposition in pipelines and equipment creates several challenges, causing issues during the production, transportation, and refining of waxy crude oil. On the other hand, conventional chemicals such as alkylphenol ethoxylates (APEs) and volatile organic compounds (VOCs) used in the treatment have negative environmental and human health effects. Nanocomposites of polymers have emerged as promising solutions to mitigate wax damage. They represent a revolutionary class of nanocomposite hybridized polymer matrices. Moreover, to our knowledge, there has been a lack of comprehensive reviews of researchers who have combined and evaluated the effectiveness of these methods over the last decade. To gain a comprehensive understanding of the current state of knowledge and recognize emerging research trends, in this systematic review, we critically evaluated the published research on the role of polymer nanocomposites in the environmentally friendly management of wax deposition in crude oil systems. This review covers numerous topics, including (1) spatiotemporal distribution of research on polymer nanocomposites, (2) synthesis routes of millennium polymer nanocomposites, (3) reaction mechanisms for wax improvement, (4) common emerging trends in applications, (5) diverse polymer candidates for nanomaterials, (6) trending nanoparticle candidates for polymerization, and (7) future perspectives. However, further progress in understanding the effects of polymer nanocomposites on waxy crude oil is hindered by the lack of comparative studies on their reaction mechanisms and human health toxicity. However, despite these limitations, polymer nanocomposites continue to show great promise in addressing challenges related to waxy crude oil.